Effects of vegetarian diet-associated nutrients on gut microbiota and intestinal physiology - Wei Xiao; Qingsong Zhang; Leilei Yu; Fengwei Tian; Wei Chen; Qixiao Zhai (Food Science and Human Wellness)
People are increasingly aware of the role of vegetarian diets in modulating human gut microbial abundance and intestinal physiology. A plant-based diet is thought to benefit host health by contributing to establish a diverse and stable microbiome. In addition, microbe-derived metabolites of specific nutrients known to be abundant in vegetarian diets (such as indigestible carbohydrates, arginine, and others) are important to promote effective intestinal immune responses, maintain intestinal barrier function, and protect against pathogens. This review explores the characteristics of the gut microbiome formed by vegetarian diets and the effects of diet-associated nutrients on intestinal microbial abundance. The interactions between the microbe-derived metabolites of vegetarian diet-associated nutrients and intestinal physiology are also discussed.